Language, Identity, and Education: Exploring Students’ Linguistic Repertoires in Multilingual Indonesian Communities - Maharani, Intan; Rizal, Ahmad; Putri, Rika; Ramadhan, Yusuf (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2023)
Indonesia’s multilingual landscape offers a dynamic site for exploring how language, identity, and education intersect in everyday life. This study examines how students in multilingual Pontianak, West Kalimantan, construct and negotiate their linguistic repertoires across school, home, and religious domains, and how these repertoires reflect broader ideologies of language and belonging. Employing a qualitative ethnographic approach within a multi-site case study design, the research was conducted in four secondary schools representing public, Islamic, and Catholic institutions. Data were collected through participant observation, semi-structured interviews, language portrait and mapping activities, and classroom discourse analysis involving students, teachers, and administrators. Findings reveal that students possess fluid and hybrid linguistic repertoires shaped by their sociocultural environments. While local Melayu dialects dominate informal communication, Bahasa Indonesia and English function as symbols of academic legitimacy and modernity, and Arabic indexes religious identity. Institutional language policies, however, often reinforce hierarchical ideologies that marginalize local languages. The study introduces the Multilayered Linguistic Repertoire Model (MLRM), which conceptualizes multilingualism as dynamic identity practice rather than discrete linguistic systems. The model advances theoretical and pedagogical contributions to language policy, literacy education, and sociolinguistic research in postcolonial contexts, underscoring the need for inclusive and culturally grounded approaches to multilingual education in Indonesia.